2000
DOI: 10.1111/1468-0033.00288
|View full text |Cite
|
Sign up to set email alerts
|

The ‘expert visitor’ concept

Abstract: Visitor studies have moved far beyond the simple gathering of statistics to develop increasingly refined data and behavioural profiles. The Centre for Study and Research on Exhibitions and Museums (Centre d'Études et de Recherche sur les Expositions et les Musées, CEREM) at Jean Monnet University, Saint‐Étienne, France, is a leader in the field and developed an innovative approach to shed new light on an old question: How do visitors perceive an exhibition?. Jean Davallon 1 is professor of sociology at the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As studies of guest books in the West have shown, the comments made here refer primarily to the display and to the content of what is on show. In the books we often encounter 'expert visitors' (Davallon et al 2000) who have developed an overview through comparisons between museums and believe this empowers and entitles them to offer profound criticism of the exhibition, its design and the curatorial approach. Particularly in the guest books in historical museums and memorials we also encounter visitors who acquire their expertise from their personal biographies or from their (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…As studies of guest books in the West have shown, the comments made here refer primarily to the display and to the content of what is on show. In the books we often encounter 'expert visitors' (Davallon et al 2000) who have developed an overview through comparisons between museums and believe this empowers and entitles them to offer profound criticism of the exhibition, its design and the curatorial approach. Particularly in the guest books in historical museums and memorials we also encounter visitors who acquire their expertise from their personal biographies or from their (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…It is true that we are all exposed to fleeting references to extremely violent past events, and it would be good to draw lessons from them: whether from novels, the media, or the commemorations designed to reach a broad "national" public. But the few social science studies that exist clearly demonstrate that memorial events primarily concern two groups: first students, who are a "captive" audience, and second, retired people and professionals, a "faithful" and "expert" audience (Davallon, 2000;Eidelmann and Raguet-Candito, 2002). Even the supposedly most attractive incarnations of these policies struggle to attract large numbers.…”
Section: Chapter 2: Memory Policies In Actionmentioning
confidence: 99%
“…Among the visitors who were not yet retired, only 1.8% were working class; inversely, 34% were managers or senior intellectual professionals. Finally, a large number were ‘expert visitors’ (Davallon et al, 2000), with 80% attending more than one historical exhibition a year, 37% more than three, 45% saying they were passionate about history and 40% saying they were particularly interested in the history of WWII.…”
Section: Who Visits Holocaust History?mentioning
confidence: 99%